Od badań podstawowych do zastosowań przemysłowych : rozwój analityki SAS - Kociuba, Łukasz (From Fundamental Researches to Industry Solutions : Development of SAS Analytics, 2007)
Invoking SAS® Industry Specific Intelligence Solutions conception article describes development of SAS Analytics from statistical package, econometric package, operation research application or statistical quality control suite to advanced applications and complex solutions solving real business problems. Article stresses data and application integration as key factor of project success (or failure). Implementing SAS® Industry Specific Intelligence Solutions one can substantially reduce risk . This conception can be used as method for producing economic value in academic research projects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 90-99